Dependencia física y depresión en los adultos mayores. Hospital Pacasmayo - 2019 - Cholan Ayay, Gisela Thalia (2020)
The purpose of this research is to establish the relationship between physical dependence and depression in older adults attending the Senior Adult Program. Hospital Pacasmayo- 2019, has a sample of 99 older adults of Hospital de Pacasamyo who met the inclusion criteria. As a research methodology, the study was considered to be a descriptive, correlational and cross-sectional quantitative type. Two survey type instruments were applied: Barthel Index and Yesavage scale. The information obtained was processed in the statistical program IMB SPSS Stadistics v.25, the results were presented in table of one and double entry in numerical and percentage form concluding that 67.6 porcent of physical dependence obtained a level of slight dependence, 26.3 porcent of Depression obtained a mild level of pdepression, 56.6 porcent moderate depression and only 16.1 porcent with a severe level. To determine the type of relationship that exists between the variables, Kendall's Tau b test was used, with a significance value p = 0.000, being highly significant.